Comprehensive Prevention Of Covid 19 Services on Dairy Farms, Namorambe Subdistrict, Deli Serdang Regency (Journal of Saintech Transfer, 2021)
COVID-19 is the disease which is very contagious so that the government issued several policies to be implemented by the community, namely wearing masks, carrying out distancing, diligently washing hands, using disinfectants and eating foods that can strengthen antibodies. The service had carried out among dairy farmers in Namorambe subdistrict, Deli Serdang Regency. The activities that were conducted, i.e teaching to make biodisinfectant, making ice cream sticks enriched with hisperidin compounds derived from red guava, moringa leaves and nagami orange and making dadih which was fermented milk on bamboo tube. The targets of the activities are: 1) The community knows to make biodesinfectant as a preventive measure against covid 19 2) The community knows the benefits of the hispiridin compound which can increase the chances of the community being more resistant and stronger against covid 19, 3) The community knows the benefit of dadih and 4) Businesses on milk are developing because of the resulting product diversification. The results of the service that the dairy farmers are able in making biodisinfectants, ice cream sticks containing hispiridine compounds and curd. Thus they are able in producing and sell it. They also make these products for families so that families are healthier and avoid the attack of covid 19.